PENGARUH KUALITAS PELAYANAN MANASIK HAJI TERHADAP KEPUASAN JAMAAH HAJI DI KBIH AT-TAQWA KOTA TANGERANG - Amirudin Amirudin; Renaldi Rio Triantoro (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2022)
The purpose of this study was to find out the Hajj ritual services at KBIH At-Taqwa Tangerang City in 2019 and to find out how much influence the quality of services provided by KBIH At-Taqwa had on the satisfaction of pilgrims. This study uses a quantitative approach method. The sampling used the Purposive Sampling technique with a standard deviation of 10% which resulted in 56 respondents from the population of Hajj pilgrims at KBIH At-Taqwa in 2019. The results showed that there was a significant relationship between the quality of Hajj ritual services and the satisfaction of the pilgrims shown. with a T value of 2,005. The correlation value is 0.860. The value of the coefficient of determination is 0.740 which shows that 74% of pilgrims' satisfaction has an effect on the quality of service at KBIH At-Taqwa, while the other 26%. how much influence the quality of service provided by KBIH At-Taqwa has on the satisfaction of pilgrims. This study uses a quantitative approach method. The sampling used the Purposive Sampling technique with a standard deviation of 10% which resulted in 56 respondents from the population of Hajj pilgrims at KBIH At-Taqwa in 2019. The results showed that there was a significant relationship between the quality of Hajj ritual services and the satisfaction of the pilgrims shown. with a T value of 2,005. The correlation value is 0.860. The value of the coefficient of determination is 0.740 which indicates that 74% of pilgrims' satisfaction has an effect on the quality of service at KBIH At-Taqwa, while the other 26% is influenced by other variable factors.